Inside Islam [videorecording (DVD)] - Hufnail, Mark; Lodwick, Mitch; Lodwick, Mitch; David, Keith (A & E Television Networks : Distributed by New Video, 2002)
It is the second largest religion in the world. Its name is derived from the word for peace, yet to many Westerners, it is synonymous with violence and terror. Widely practiced and equally widely misunderstood, Islam is a religion that has been at the heart of human experience for well over a thousand years. In the world after September 11th, it is especially critical to understand the origins and practice of Islam, and its role in the world today. This balanced, objective introduction to the great faith traces its roots back to the Hebrew Bible and explains the main tenets of Islam: the Five Pillars that all Muslims must adhere to. Discover what the Qur'an has to say about war, violence and suicide, and see how these words have been co-opted by extremists. Running time 93 minutes, with commentary from September 2001 for 9 minutes after.